2018
DOI: 10.1534/g3.118.200462
|View full text |Cite
|
Sign up to set email alerts
|

Complex Haplotypes of GSTM1 Gene Deletions Harbor Signatures of a Selective Sweep in East Asian Populations

Abstract: The deletion of the metabolizing Glutathione S-transferase Mu 1 (GSTM1) gene has been associated with multiple cancers, metabolic and autoimmune disorders, as well as drug response. It is unusually common, with allele frequency reaching up to 75% in some human populations. Such high allele frequency of a derived allele with apparent impact on an otherwise conserved gene is a rare phenomenon. To investigate the evolutionary history of this locus, we analyzed 310 genomes using population genetics tools. Our anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Previous studies revealed that the GSTM family of genes have critical roles in several cancer types. GSTM1 is highly polymorphic in humans and is associated with multiple cancer types, such as bladder and breast cancer, metabolic disorders and autoimmune diseases, as well as anticancer drugs response and resistance ( 28 ) GSTM1 deletion in humans was indicated to have a key role in bladder ( 29 ) and breast cancer ( 30 , 31 ), multiple sclerosis ( 32 ), severe early-onset mental disorders including schizophrenia-spectrum disorder, bipolar disorder with psychotic symptoms or first-episode psychosis ( 33 ) and acute myeloid leukemia ( 34 ). Csejtei et al ( 35 ) identified that GSTM1 may be a prognostic biomarker in clinical diagnostics as well as a potential therapeutic candidate in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the GSTM family of genes have critical roles in several cancer types. GSTM1 is highly polymorphic in humans and is associated with multiple cancer types, such as bladder and breast cancer, metabolic disorders and autoimmune diseases, as well as anticancer drugs response and resistance ( 28 ) GSTM1 deletion in humans was indicated to have a key role in bladder ( 29 ) and breast cancer ( 30 , 31 ), multiple sclerosis ( 32 ), severe early-onset mental disorders including schizophrenia-spectrum disorder, bipolar disorder with psychotic symptoms or first-episode psychosis ( 33 ) and acute myeloid leukemia ( 34 ). Csejtei et al ( 35 ) identified that GSTM1 may be a prognostic biomarker in clinical diagnostics as well as a potential therapeutic candidate in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CNVs impacting GSTM1 and UGT2B17 are polymorphic in humans and chimpanzees, suggesting inter‐species balancing selection. However, further analyses revealed that deletions of GSTM1 arose separately in both lineages (Saitou, Satta, & Gokcumen, 2018; Saitou, Satta, Gokcumen, & Ishida, 2018), while the evolutionary history of UGT2B17 remains unknown.…”
Section: Contributions Of Structural Variation To Human Evolution Ada...mentioning
confidence: 99%
“…Most studies primarily interrogate single-nucleotide variants and SVs are often considered if only a “tag” single-nucleotide variant can be found. For example, our work has resolved the complex evolutionary history of the common deletion of the metabolizing GSTM1 gene ( Saitou, Satta, and Gokcumen 2018 ). Locus-specific studies showed a strong association between this deletion and bladder cancer (The GSTM1 deletion is the risk allele, P = 4 × 10 −11 ) ( Rothman et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to the lack of single-nucleotide variants tagging this deletion, most genome-wide association studies and traditional selection scans did not include this deletion. Investigating individual haplotypes that harbor the deletion led us to identify one particular haplotype associated with the deletion that has been subject to a recent selective sweep in the East Asian populations ( Saitou, Satta, and Gokcumen 2018 ).…”
Section: Introductionmentioning
confidence: 99%